2003
DOI: 10.2113/gscanmin.41.3.649
|View full text |Cite
|
Sign up to set email alerts
|

On Type Romarchite and Hydroromarchite From Boundary Falls, Ontario, and Notes on Other Occurrences

Abstract: The type material of romarchite and hydroromarchite from Boundary Falls, Winnipeg River, Ontario, Canada, was re-examined. The minerals form deposits on pewter bowls and are products of tin corrosion in a unique cold freshwater environment. Type romarchite is very fine-grained and replaces pseudotetragonal crystals of an unknown precursor. Revised X-ray powderdiffraction data are consistent with the accepted tetragonal symmetry and space group P4/nmm, and provide the refined unit-cell parameters a 3.8014(3), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Černý et al (1988) reviewed the occurrence of divalenttin minerals in granitic pegmatites, and concluded that conditions of exceptionally low oxygen fugacity are required for their formation. Abhurite, hydroromarchite and romarchite generally have an anthropogenic origin, being derived from the corrosion of tin, bronze, or pewter artifacts (Ramik et al 2003), commonly in a marine environment, e.g., relics on sunken ships (Dunkle et al 2003(Dunkle et al , 2004. Rarely, romarchite occurs as a natural (non-anthropogenic) product from the alteration of native tin, or as a replacement of the tin sulfi de herzenbergite (cf.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Černý et al (1988) reviewed the occurrence of divalenttin minerals in granitic pegmatites, and concluded that conditions of exceptionally low oxygen fugacity are required for their formation. Abhurite, hydroromarchite and romarchite generally have an anthropogenic origin, being derived from the corrosion of tin, bronze, or pewter artifacts (Ramik et al 2003), commonly in a marine environment, e.g., relics on sunken ships (Dunkle et al 2003(Dunkle et al , 2004. Rarely, romarchite occurs as a natural (non-anthropogenic) product from the alteration of native tin, or as a replacement of the tin sulfi de herzenbergite (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, romarchite occurs as a natural (non-anthropogenic) product from the alteration of native tin, or as a replacement of the tin sulfi de herzenbergite (cf. Ramik et al 2003). In the type material, romarchite occurs as a fi ne-grained black pseudomorph after a lower-symmetry species (Ramik et al 2003); the precursor is likely to have been the metastable orthorhombic polymorph of romarchite, red stannous oxide (cf.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations